Assessment of tuberculosis biomarkers in paratuberculosis-infected cattle - Klepp, Laura Ines; Colombatti Olivieri, Maria Alejandra; Moyano, Roberto Damian; Romano, Maria Isabel; Malovrh, Tadej; Ocepek, Matjaž; Blanco, Federico Carlos; Bigi, Fabiana (Sciendo, 2023)
Introduction: Mycobacterium bovis and Mycobacterium avium subsp. paratuberculosis, respectively the causative agents of bovine tuberculosis (bTB) and bovine paratuberculosis (PTB), share a high number of antigenic proteins. This characteristics makes the differential diagnosis of the diseases difficult. The interferon gamma (IFN-γ), C-X-C motif chemokine ligand 10 (CXCL10), matrix metallopeptidase 9 (MMP9), interleukin 22 (IL-22) and thrombospondin 1 (THBS1) bovine genes have already been shown to be accurate transcriptional biomarkers of bTB. In order to improve the diagnosis of bTB and PTB, in the present study we evaluated the risk of false positivity of these bTB biomarkers in cattle with PTB. Material and methods: The transcription of these genes was studied in 13 PTB-infected cattle, using Mycobacterium avium subsp. paratuberculosis (MAP)-stimulated peripheral blood mononuclear cells (PBMC). Results: Overall, the levels of IFN-γ, CXCL10, MMP9 and IL-22 transcripts in MAP-stimulated PBMC failed to differentiate animals with PTB from healthy animals. However, as bTB-afflicted cattle do, the MAP-infected group also displayed a lower level of THBS1 transcription than the non-infected animals. Conclusion: The results of this study add new specificity attributes to the levels of transcription of IFN-γ, CXCL10, MMP9 and IL-22 as biomarkers for bTB.